Paul Fayerabend's "Anything Goes" Epistemology Its Relevance in Knowledge Development - Nazar Husain Hadi Pranata Wibawa (Jurnal Madania, 2024)
This article seeks to demonstrate the applicability of Paul Feyerabend's "anything goes" epistemology to the development of knowledge. This study is a literature review. Data were collected through data inventory, then analyzed and interpreted. The results of the study show that "all methodologies have limitations, and the only 'rule' that can survive is 'anything goes'". The main idea of anything goes is, first, the recommendation proposed by Feyerabend related to the discourse of anything goes, only remains as a negative freeing recommendation because it requires a certain scientific situation that is considered to restrict scientists; and is often understood simply as advocating the absence of laws, methodologies, and rules in science. Second, it actually limits the movement of scientists because it requires participation only in practices that are undefined and cannot be defined. Third, it is only a consequence of the first and second premises. In other words, anything goes, both externally and internally, contains two dimensions of freedom at once. The differences in position must be clarified to avoid confusion about the status of freedom contained in anything goes.